BURNOUT TO EMPOWERMENT: TRANSFORMATIVE LEARNING PATHWAYS IN EFL TEACHERS (SCIENCE TIME JOURNAL, 2026)
Teacher burnout has emerged as one of the most pressing challenges in English as a Foreign Language (EFL) education, influencing teacher performance, learner outcomes, and institutional effectiveness. Recent scholarship demonstrates that transformative learning—through reflection, emotional awareness, and identity reconstruction—offers a pathway from burnout to empowerment. Drawing upon nine peer-reviewed studies published between 2022 and 2025, this article explores (a) the causes and early indicators of burnout, (b) the psychological and emotional mechanisms mediating resilience, (c) the role of transformative learning and identity work in empowerment, and (d) practice-embedded strategies that sustain teacher well-being. The findings underscore the significance of reflective practice, growth mindset, collegial collaboration, and continuous professional learning communities in cultivating empowered EFL teachers capable of thriving amid pedagogical and technological change.